Kepemimpinan Transformasional dalam Meningkatkan Kepuasan Kerja Perawat pada Sistem Pelayanan Kesehatan - Fauzia, Liza; Sabil, Fitri A.; Abrar, Eva Arna; Anisa, Nurul Rezki; Kadrianti, Erna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the relationship between transformational leadership and nurse job satisfaction in healthcare settings. The method used is a systematic review using the Pubmed, Science Direct, google scholar, EBSCO, and ProQuest databases. The results of the study were obtained from 7 articles that met the inclusion criteria, based on the results of the article analysis, it was found that transformational leadership style showed a positive correlation with nurse job satisfaction, leaders who apply transformational leadership style have a positive impact on work performance that results in job satisfaction and overall improves the quality of nurse work so that it has an impact on job satisfaction and the quality of nursing care. In conclusion, the transformational leadership style makes a significant contribution to increasing nurse self-confidence and motivation, which ultimately has a positive effect on performance and job satisfaction. Keywords: Leadership, Job Satisfaction, Nurses, Transformational Health Care System